Impact of well-controlled type 2 diabetes mellitus on quality of life of chronic periodontitis patients - Leila Cristina Mourao; Elanne Garcia; Daniela Passos; Thamirys Lorena; Antonio Canabarro (Wolters Kluwer Medknow Publications, 2016)
Background: The purpose of the study is to examine the quality of life (QoL) in chronic periodontitis (CP) patients associated with or not with well-controlled type 2 diabetes mellitus (DM2). Materials and Methods: Five hundred CP patients, 250 with DM2 (GDM2 group) and 250 age- and gender-matched controls without DM2 (GND), were enrolled in this cross-sectional case-controlled study from January to September 2015. They were interviewed by a QoL questionnaire (Functional Assessment of Chronic Illness Therapy-Fatigue) validated to Portuguese. Periodontal examinations were also performed to confirm CP: probing pocket depth and clinical attachment level must be> 3 mm. Results: An association between the presence of DM2 and a high negative impact on QoL was observed. All domains in GDM2 patients presented mean values above 19. On the other hand, three functional domains in GND (physical, social/family, and emotional) showed values below 19 (medium negative impact). Comparisons between GND and GDM2 revealed the statistical difference between them for all domains (P < 0.05). Conclusions: This study shows that DM2 associated with CP negatively affect QoL, even considering well-controlled diabetic patients.